Analyzing root traits to characterize juniper expansion into rangelands - Chesus, Kelly A., author; Ocheltree, Troy, advisor; Comas, Louise, committee member; Knapp, Alan, committee member (Colorado State University. Libraries, 2016)
Juniper expansion into sagebrush communities is a widespread phenomenon occurring across large regions of the western U.S. over the past century. Fire suppression and increased grazing activity are commonly considered as the primary drivers of expansion but they do not explain all instances of expansion. In order to develop a complete explanation for the success of juniper we investigated the competitive abilities of J. osteosperma (Utah juniper) and A. tridentata (big sagebrush) based on fine root traits, including specific root length (SRL), fine root diameter, and fine root biomass, and spatial patterns of water use inferred from stem and soil stable oxygen isotopes (δ18O). Data were collected from three different age classes of J. osteosperma (seedling, sapling, and mature) to better understand the competitive abilities at different life stages. J. osteosperma age classes were originally determined by height and later aged from cross sections. The youngest seedling in our study was 14 years of age, therefore we refer to the seedlings in this study as 'advanced.' Advanced J. osteosperma seedlings demonstrated the ability to switch their reliance from shallow to deep water sources later in the season, potentially enhancing their survival particularly during drought events. A. tridentata had traits associated with faster root proliferation and resource acquisition (significantly greater SRL and smaller root diameter) suggesting competition for limiting resources is likely not a primary driver of expansion of J. osteosperma.